Diverse potential of secretome from natural killer cells and monocyte-derived macrophages in activating stellate cells - Sauer, Julia; Steixner-Kumar, Agnes A.; Gabler, Svenja; Motyka, Maciej; Rippmann, Jörg F.; Brosa, Stefan; Boettner, Dennis; Schönberger, Tanja; Lempp, Charlotte; Frodermann, Vanessa; Simon, Eric; Krenkel, Oliver; et al. (Frontiers in Immunology, 2024)
Chronic liver diseases as non-alcoholic steatohepatitis (NASH)-induced cirrhosis are characterized by an increasing accumulation of stressed, damaged, or dying hepatocytes. Hepatocyte damage triggers the activation of resident immune cells, such as Kupffer cells (KC), as well as the recruitment of immune cells from the circulation towards areas of inflammation. After infiltration, monocytes differentiate into monocyte-derived macrophages (MoMF) which are functionally distinct from resident KC. We herein aim to compare in vitro signatures of polarized macrophages and activated hepatic stellate cells (HSC) with ex vivo derived disease signatures from human NASH. Further, to shed more lights on HSC activation and liver fibrosis progression, we investigate the effects of the secretome from primary human monocytes, macrophages and NK cells on HSC activation. IL-4 and IL-13 treatment induced TGF-β1 secretion by macrophages.However, the supernatant transfer did not induce HSC activation. Interestingly, PMA-activated macrophages showed a strong induction of the fibrosis response genes COL10A1 and CTGF, while supernatant of IL-4/IL-13 treated monocytes induced the upregulation of COL3A1 in HSC.Supernatant of PMA-activated NK cells had the strongest effect on COL10A1 induction in HSC, while IL-15 stimulated NK cells reduced the expression of COL1A1 and CTGF. These data indicate that other factors, aside the well-known cytokines and chemokines, might potentially be stronger contributors to activation of HSCs and induction of a fibrotic response, indicating a more diverse and complex role of monocytes, macrophages and NK cells in liver fibrosis progression. Highlights  Comprehensive analysis of RNASeq derived gene signatures of in vitro activated primary human monocytes, macrophages, hepatic stellate cells and human NASH liver biopsies provides novel insights into the role of immune cell-mediated fibrosis progression.  Pairwise gene-cluster enrichment analysis indicates a continuous loss of IL-4/IL-13 polarized monocyte-derived macrophage signature during fibrosis progression in human NASH liver biopsies. In comparison to monocytes and monocyte-derived macrophages, NK cells display more prominent potential in activating primary human hepatic stellate cells in vitro. Monocyte-derived macrophages and NK cells overactivated by PMA induce a strong fibrotic response in primary human HSC, while IL-4/IL-13 polarized cells lack this ability.